Silver lining as a predictor of mental health outcomes among caregivers of patients with mental disorders - Shafiq, Muhammad Haseeb (Journal of Pakistan Psychiatric Society, 2026)
ABSTRACT ObjectiveTo understand the relationship and predictive role of silver lining on mental health outcomes among caregivers of patients with mental disorders.Study designCross-sectional correlational research design.Place and duration of StudyInpatient and outpatient settings of the psychiatric unit of Allied Hospital 2, Faisalabad, from August 2025 to September 2025.Subjects and Methods200 family caregivers of individuals diagnosed with mental disorders, for at least 6 months, aged 18 years and above, both male and female, took part in the study. Participants were enrolled through a purposive sampling technique. General Health Questionnaire-28 (GHQ-28)1 and silver lining scales (SLS)2 were utilised to measure the outcome variables. SPSS version 25 was used, and ethical issues were addressed according to the IRB of the institute.ResultsSignificant negative correlation was found between silver lining and its sub-scales, and mental health outcomes and its sub-scales. Multiple linear regression revealed that personal growth and familial bonding were significant negative predictors of poor mental health outcomes. But empathy emerged as a significant positive predictor. The final model accounted for 18% of the variance in mental health outcomes.ConclusionSilver lining in the caregiving experience, particularly through personal growth and familial bonding, can mitigate negative mental health outcomes among caregivers of individuals with mental disorders. This highlights the protective role of positive psychological resources.